2010
DOI: 10.4238/vol9-2gmr766
|View full text |Cite
|
Sign up to set email alerts
|

Amplified fragment length polymorphism analysis of grapevine rootstock genotypes in Turkey

Abstract: ABSTRACT. Amplified fragment length polymorphism (AFLP) technique was used to assess genetic relationships among 20 grapevine rootstocks in Turkey. Discrimination of the rootstocks with 10 primer combinations yielded 1366 bands on AFLP gels; 65% of them were polymorphic. The rootstocks revealed two main clusters; one of them comprised two (Malégue and Harmony) and the other 18 genotypes. The Ber x Rip hybrids Cosmo 2 and Cosmo 10 formed a group with a high internal similarity ratio (0.909); they also formed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Among the tested primers, E-ACT x M-CTG, E-ACT x M-CTT, E-AAC x M-CAA, E-AAC x M-CAC, E-AAC x M-CAG and E-AAC x M-CAT were important combinations for either germplasm screening, landrace accessions, inbred lines and other studies like genetic mapping and molecular assisted selection. These results are in agreement with others crop such as grapevine (ERGÜL et al, 2010), where 4 single and 20 double AFLP-primer combinations were shown to be successful discriminate 20 rootstocks; and soybean, where it was possible to discriminate each one of the 44 soybean genotypes using five AFLP-primer combinations (SINGH et al, 2010).…”
Section: Resultssupporting
confidence: 91%
“…Among the tested primers, E-ACT x M-CTG, E-ACT x M-CTT, E-AAC x M-CAA, E-AAC x M-CAC, E-AAC x M-CAG and E-AAC x M-CAT were important combinations for either germplasm screening, landrace accessions, inbred lines and other studies like genetic mapping and molecular assisted selection. These results are in agreement with others crop such as grapevine (ERGÜL et al, 2010), where 4 single and 20 double AFLP-primer combinations were shown to be successful discriminate 20 rootstocks; and soybean, where it was possible to discriminate each one of the 44 soybean genotypes using five AFLP-primer combinations (SINGH et al, 2010).…”
Section: Resultssupporting
confidence: 91%
“…Molecular characterization in rootstocks is mainly employed to compare other V. vinifera cultivars from collections in the largest germplasm banks of Vitis. Molecular markers, such as restriction fragment length polymorphism (RFLP) (Bourquin, Otten, & Walter, 1991;Bourquin, Tournier, Otten, & Walter, 1992;Guerra & Meredith, 1995), inter simple sequence repeat (ISSR) (Alizadeh, Singh, Jhang, & Sharma, 2008), amplified fragments length polymorphism (AFLP) (Ergül, Aras, & Söylemezoğlu, 2010;Sabir, Doğan, Tangolar, & Kafkas, 2010), simple repeated sequences (SSR) (Sefc, Regner, Glössl, & Steinkellner, 1998;Dzhambazova et al, 2007;Laucou et al, 2011;Jahnke, Majer, Varga, & Szöke, 2011;Andre et al, 2012;Sant'Ana et al, 2012;Emanuelli et al, 2013;Barankova, 2014), and some methods based on retrotransposons (Guo, Guo, Hou, & Zhang, 2014), have been used to identify polymorphic loci for the measurement of genetic divergence or similarity between rootstock varieties.…”
Section: Introductionmentioning
confidence: 99%